Traditional Chinese medicine for treatment of sepsis and related multi-organ injury - Song, Yaqin; Lin, Weiji; Zhu, Wei (Frontiers in Pharmacology, 2023)
Sepsis is a common but critical illness in patients admitted to the intensive care unit and is associated with high mortality. Although there are many treatments for sepsis, specific and effective therapies are still lacking. For over 2,000 years, traditional Chinese medicine (TCM) has played a vital role in the treatment of infectious diseases in Eastern countries. Both anecdotal and scientific evidence show that diverse TCM preparations alleviate organ dysfunction caused by sepsis by inhibiting the inflammatory response, reducing oxidative stress, boosting immunity, and maintaining cellular homeostasis. This review reports on the efficacy and mechanism of action of various TCM compounds, herbal monomer extracts, and acupuncture, on the treatment of sepsis and related multi-organ injury. We hope that this information would be helpful to better understand the theoretical basis and empirical support for TCM in the treatment of sepsis.